2006
DOI: 10.1007/s11604-006-0061-y
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem computed tomography for detecting causes of sudden death in infants and children: retrospective review of cases

Abstract: The causes of sudden death in infants and children were detected at a high rate when we comprehensively investigated the PMCT and other examination findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Postmortem imaging for detecting cause of death has been introduced into forensic examination, however only a few clinical studies have been reported on using postmortem MDCT in ED [26,27,29]. To the best of our Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Postmortem imaging for detecting cause of death has been introduced into forensic examination, however only a few clinical studies have been reported on using postmortem MDCT in ED [26,27,29]. To the best of our Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Postmortem imaging may contribute important new information and may even, in some cases, be an acceptable substitute for a traditional autopsy [3-5, 8, 11, 15, 17-19]. Although several reports of postmortem imaging for clinical application have been published [14,[21][22][23][24][25][26][27][28][29], to the best of our knowledge, there have been few studies of the usefulness of postmortem MDCT on nontraumatic death in the emergency setting [26,27,29]. The aim of this study was to investigate the diagnostic performance and the limitations of postmortem MDCT in the detection of fatal findings related to causes of nontraumatic sudden or rapid death in ED, and with the aim of comparing the findings on postmortem MDCT with those of traditional autopsy.…”
Section: Introductionmentioning
confidence: 99%
“…Given the origin of the study, this can be equated as equivalent to within two hours of confirmation of death. 18 A possible cause of the historical notion of "cot death" was that of airway occlusion whilst sleeping. A factor that has dramatically reduced the incidence of sudden infant death syndrome in the UK is a recommendation to ensure babies sleep on their backs, an intervention that stretches back to the mid 1990s.…”
Section: Discussionmentioning
confidence: 99%
“…However there has been little focus on post-mortem imaging specifically for paediatric populations, and only one study (31) has focused on PMCT for detecting causes of sudden death in infants and children (15 patients, and an autopsy was conducted on 2).…”
Section: Considerations Specific To Pediatric Pathology -Sudimentioning
confidence: 99%